A methodology to prevent cascading contingencies using BESS in a renewable integrated microgrid. (September 2019) - Aziz, Tareq; Masood, Nahid-Al; Deeba, Shohana Rahman; Tushar, Wayes; Yuen, Chau
Highlights: A methodology for BESS placement to prevent cascading contingencies and blackout. Implications of grid codes on the islanded operation of a microgrid are explored. Effectiveness of the proposed methodology is demonstrated via simulations. Abstract: One of the key features of a microgrid is its capability to operate in an islanded mode when required. However, due to limited resources and bidirectional power flows, a microgrid in islanded mode is susceptible to different contingencies with extensive effects, e.g., cascading loss of distributed generators (also known as Distributed Energy Resources – DERs) due to unacceptable post-fault voltage recovery performance. In a renewable integrated microgrid, conventionally Battery Energy Storage System (BESS) is placed at the point of common coupling of distributed generators. However, such a placement approach does not prevent the cascading tripping of DERs following a fault, especially in the presence of a large share of induction motor loads. To address this challenge, this paper proposes a new placement methodology of BESS based on reactive power margin to prevent cascading contingencies and a subsequent blackout in a microgrid. The proposed methodology deploys an iterative technique. If the voltages at DERs terminals after a fault fail to recover within the stipulated time suggested by the grid code, BESS is placed at the bus with the lowest reactive power margin. It is known as the centralised placement approach of BESS. If this approach does not avert the DER tripping, the location of BESS is changed using the distributed placement scheme. In this scheme, several BESSs are placed on multiple buses, which have relatively lower values of reactive power margin. In a specific microgrid, either the centralised or the distributed BESS placement approach is eventually adopted. To explore the effectiveness of the proposed method, the IEEE 43 bus industrial test system integrated with renewable energy resources is considered as an islanded microgrid for simulations. It is found that the proposed approach results in the most appropriate placement of BESS to make the microgrid immune to cascading tripping of DERs.